Faktor-Faktor Yang Memengaruhi Empati Pada Individu - Rohi, Ensely Mega Wenyi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Empathy is an important socio-emotional ability in human life as it relates to the capacity to understand and share the emotional experiences of others. Empathy plays a role in building harmonious social relationships and encouraging the emergence of prosocial behavior. This study aims to examine the factors that influence empathy in individuals through a literature review approach. The method used in this study is a literature review by examining various sources such as journal articles and books relevant to the research topic. Data were collected through literature searches from various scientific sources and analyzed descriptively by identifying and synthesizing findings related to factors influencing empathy. The results of the review indicate that empathy in individuals is influenced by various internal and external factors, including personality, surrounding environment, interpersonal relationships, communication skills, role models, gender, social experience, education, family environment, age, socialization, and culture. These factors indicate that empathy develops through the interaction between individual characteristics and social experiences in everyday life.